Respuesta :
Answer:
C: [tex]\frac{x-1}{x+3}[/tex]
Step-by-step explanation:
The simplest form of the expression below, can be found through factorization process.
[tex]\frac{x^{2}+5x-6}{x^{2}+9x+18}[/tex]
We have two quadratic expression. To find their factor, we only need to apply some steps:
Factorizing [tex]x^{2}+5x-6=(x+a)(x-b)[/tex]
We have to find to numbers a and b that multiplied result in 6, but subtracted result in 5. We can see that [tex]a = 6[/tex] and [tex]b=1[/tex] are the right numbers, because 6 times 1 equals 6, and 6 minus 1 equals 5.
Therefore, [tex]x^{2}+5x-6=(x+6)(x-1)[/tex]
On the other expression, we applied the same process:
[tex]x^{2}+9x+18=(x+6)(x+3)[/tex]; because, [tex]6(3)=18[/tex] and [tex]6+3=9[/tex]
Then, we replace these factors for each expression:
[tex]\frac{x^{2}+5x-6}{x^{2}+9x+18}[/tex]
[tex]\frac{(x+6)(x-1)}{(x+6)(x+3)}[/tex]
Eliminating similar factors, we have:
[tex]\frac{(x-1)}{(x+3)}[/tex]
Which is the simples form.